2005
DOI: 10.1111/j.1748-5967.2005.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinneret Microstructure of the Silk Spinning Apparatus in the Crab Spider, Misumenops tricuspidatus (Araneae: Thomisidae)

Abstract: The silk spinning apparatus in the crab spider, Misumenops tricuspidatus was studied with the field emission scanning electron microscope (FESEM) and the main microstructural characteristics of the silk glands are presented. In spite of the fact that the crab spiders do not spin webs to trap a prey, they also have silk apparatus even though the functions are not fully defined. The crab spider, Misumenops tricuspidatus possesses only three types of silk glands which connected through the typical spinning tubes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Based on the morphological characteristics of the silk glands as well as the spinnerets (Coddington 1986), the spinning apparatus of this spider corresponds to the patterns found in Araneidae spiders (Tillinghast & Townley 1986; Moon 1998; Moon & Kim 2005) and other web‐building spiders (Kovoor 1987; Peters & Kovoor 1991; Park & Moon 2002; Moon & An 2005). The two major ampullate glands and the pyriform glands were associated with the anterior spinnerets; the minor ampullate glands and the tubuliform and aciniform glands were associated with the median spinnerets, and the tubuliform, flagelliform, aggregate and aciniform glands were associated with the posterior spinnerets.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Based on the morphological characteristics of the silk glands as well as the spinnerets (Coddington 1986), the spinning apparatus of this spider corresponds to the patterns found in Araneidae spiders (Tillinghast & Townley 1986; Moon 1998; Moon & Kim 2005) and other web‐building spiders (Kovoor 1987; Peters & Kovoor 1991; Park & Moon 2002; Moon & An 2005). The two major ampullate glands and the pyriform glands were associated with the anterior spinnerets; the minor ampullate glands and the tubuliform and aciniform glands were associated with the median spinnerets, and the tubuliform, flagelliform, aggregate and aciniform glands were associated with the posterior spinnerets.…”
Section: Discussionmentioning
confidence: 75%
“…It has been reported that most Araneidae spiders (Tillinghast & Townley 1987; Moon 1998; Park & Moon 2002; Moon & An 2005) as well as Theridiidae spiders (Moon et al. 1998; Casem et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most eccribellate orb‐web spiders produce a gluey material from a flagelliform and two aggregate glands (Kovoor & Zylberberg 1979; Kovoor 1987; Moon & Kim 2005). However, both sexes of O. striatipes lack these so‐called “triad” spigots (Peters 1987; Peters & Kovoor 1991; Moon & Kim 2005) as do other wandering spiders such as the wolf spider Pardosa astrigera (Moon 1998), the funnel‐web spider Agelena limbata (Park & Moon 2002) and the crab spider Misumenops tricuspidatus (Moon & An 2005).…”
Section: Discussionmentioning
confidence: 99%